Insights into community assembly mechanisms, biogeography, and metabolic potential of particle-associated and free-living prokaryotes in tropical oligotrophic surface oceans - Ren, Yanhu; Luo, Zhenhao; Liu, Qian; Wei, Bin; Wu, Yue-Hong; Shu, Wen-Sheng; Xu, Xue-Wei (Frontiers in Marine Science, 2022)
Heterotrophic prokaryotes constitute the largest living biomass in the ocean and can be divided into particle-associated (PA) and free-living (FL) fractions. PA and FL prokaryotic communities play critical roles in the biogeochemical cycles of particulate and dissolved organic matter; however, their community assembly processes, biogeographical distribution patterns, and functional properties in oligotrophic surface water remain to be further elucidated. Based on 16S rRNA gene sequencing and shotgun metagenomics, we investigated the assembly mechanisms, biogeography, and functional potential of PA and FL prokaryotes in the surface waters of the West Pacific and Indian Oceans. FL prokaryotic communities were predominantly structured by deterministic processes, whereas their PA counterparts appeared to be shaped by the combined action of deterministic and stochastic processes. PA and FL prokaryotes in the tropical oligotrophic surface ocean exhibit markedly different community structures and functional potentials. Bacterial PA specialists such as Lentimonas, Alteromonas, and Pirellula as well as archaeal PA specialists Marine Group II and Marine Group III were significantly more abundant in PA assemblages, whereas lineages such as Prochlorococcus, SAR11 clade, and Candidatus Actinomarina were significantly more abundant in FL communities. The metabolic potential of the PA community was more abundant in pathways such as polyamine biosynthesis, carbohydrate metabolism, and glycosaminoglycan degradation. In contrast, the FL community was more enriched in functions related to amino acid metabolism, lipid biosynthesis, and aromatic degradation.